Elementos estructurales del derecho a la verdad. (2012)
This article refers specifically to the current state of the discussion on the basic legal structure of the right to truth; its size and degree of legality and reports initial results on the evaluation of the models adopted for peace in Colombia; in light of the international standards and practices